Dredged sediments valorisation in compressed earth blocks: Suction and water content effect on their mechanical properties. (15th January 2018) - Serbah, Boumediene; Abou-Bekr, Nabil; Bouchemella, Salima; Eid, Joanna; Taibi, Said
Highlights: Valorisation of natural dredged sediments in compressed earth blocks (CEB). Sediments were amended with sand and compacted to MPO + 25 blows. Drying-wetting paths were carried out to understand the hydro-mechanical behaviour. Relations between mechanical properties and water content or suction were established. Abstract: The silting of dams requires periodic dredging campaigns to maintain their functional capabilities. In Algeria, more than 32 million m 3 of sediment are deposited every year. In this paper, we investigate the case of the Bakhadda dam in western Algeria, whose dredged sediments can be valorised as an eco-geo-material for building construction in the form of compressed earth blocks (CEB). Preliminary hydro-mechanical study showed the need to amend the natural sediment with sand fraction up to 30% to reach the recommended characteristics of the standards, as granulometry, plasticity and mechanical properties. To achieve high mechanical strength, compaction energy equivalent to modified optimum proctor + 25 blows was required. The hydro-mechanical properties of the manufactured CEB were then studied. Water content effect on their mechanical properties was highlighted. In fact, the strength increases when water content decreases due to an increase in suction. Using the measured drying-wetting paths, relations were established between small strains modulus and water content and suction. Results of this study have led to the valorisation of natural dredged sediments in CEB which respond to the recommendations. Based on the hydric and mechanical tests carried out, the behaviour of CEB in situ was determined.